Optimal timing for cataract surgery in patients with thyroid-associated ophthalmopathy - Na Miao; Yan-Chi Chen; Wei-Min He (International Journal of Ophthalmology)
AIM: To investigate the optimal timing and therapeutic effects of cataract surgery in patients with moderate to severe thyroid-associated ophthalmopathy (TAO). METHODS: Data from TAO patients who underwent cataract surgery between 2014 and 2024 were analyzed. patients were categorized into two groups based on the hospital where their cataract surgery was performed: an external hospital surgery group and an in-house hospital surgery group. Patients in external hospital presenting with complications within six months postoperatively were assessed for clinical features, imaging, thyroid function, and outcomes. Patients who underwent surgery at West China Hospital were evaluated for clinical status, imaging, laboratory findings, and manifestations. RESULTS: In the external hospital group (n=31), common symptoms included eyelid swelling (64.52%) and diplopia (51.61%), with restricted eye movement in all patients. Most patients were in the active stage (87.10%) and exhibited various complications, such as dysthyroid optic neuropathy (DON) in 4 patients, misdiagnosis of glaucoma in 1 patient, and enucleation due to fungal infection in 1 patient. In the West China Hospital group (n=30), 2 patients were in the active stage, and 28 were in the inactive stage. Postoperative visual acuity improved in 36 eyes, except for in 2 eyes with DON. Active TAO patients with mature cataracts had effective inflammation control and no complications at the 6-month follow-up. CONCLUSION: In patients with moderate to severe active TAO complicated by cataracts, delaying cataract surgery until 6mo of TAO control should be considered if cataracts are stable. Simultaneous anti-inflammatory treatment and cataract surgery should be performed for mature/hypermature cataracts, and TAO management should be continued after surgery.